Las estrategias metodológicas y su incidencia en el logro de destrezas con criterio de desempeño del bloque curricular el agua, un medio de vida en el área de ciencias naturales de los niños de quinto grado de educación general básica de la escuela Simón Rodrìguez de la parroquia Sabiango, del cantón Macará, provincia de Loja. Periodo 2013-2014 - Guarnizo Novillo, Stalin Fabricio (2015)
This research deals with: THE METHODOLOGICAL STRATEGIES AND ITS IMPACT ON THE ACHIEVEMENT OF SKILLS WITH PERFORMANCE CRITERIA BLOCK CURRICULUM "WATER, A WAY OF LIFE" IN THE AREA OF NATURAL SCIENCE OF FIFTH GRADERS BASIC GENERAL EDUCATION SCHOOL "SIMON RODRIGUEZ" SABIANGO PARISH, CANTON MACARÁ AND PROVINCE OF LOJA. PERIOD 2013-2014, the same that worked with the following objective, determine how to operationalize methodological strategies to improve the development of skills with performance criterion in the curricular area "Water means life" in the Department of Natural Sciences of the fifth graders of General Basic Education of "Simon Rodriguez" School of Sabiango parish, canton and province of Loja Macara. 2013-2014 period, let me clarify different approaches have been applying the skills of teachers in the curricular area "Water means life" in the area of Natural Sciences; Likewise, we worked with the following methods, scientific, inductive, deductive, analytic-synthetic, statistical; the same that allowed me to analyze and describe the research. He also worked with a survey of teachers and students to get information about the issues raised to. Toso this research work can be said that teachers do not handle appropriate methodologies according to content that allows students to develop skills with performance criteria of curricular block the "Water means life" in the area of Natural Sciences